Pengaruh Persepsi Dan Literasi Ekonomi Syariah Terhadap Minat Wirausaha (Studi Kasus Pada Siswa Kelas XII SMA Darul Falah Cihampelas, Bandung Barat) - Hidayat, Taufik; Gandana, Deden; Ihwanudin, Nandang (Universitas Islam Kadiri, 2025)
Abstract This study aims to analyze the influence of perception and Islamic economic literacy on students' interest in entrepreneurship. The focus of the study was directed at grade XI students of SMA Darul Falah Cihampelas. The approach used was quantitative with an associative method. Data collection was carried out by distributing questionnaires to 135 respondents. The results of the study showed that partially, the perception of Islamic economics did not have a significant effect on students' interest in entrepreneurship. On the contrary, Islamic economic literacy had a significant effect on interest in entrepreneurship. Simultaneously, perception and Islamic economic literacy together had a significant effect on students' interest in entrepreneurship. This finding indicates the importance of increasing Islamic economic literacy in encouraging entrepreneurial spirit among students. Keywords: Perception, Islamic economic literacy, Interest in entrepreneurship